Prevalencia de parásitos gastrointestinales en ovinos en el camal de Saquisili. - Rodríguez Ovallos, Tatiana (2021)
Parasitic infections are the main causes of diseases and productivity losses in sheep farms in Ecuador. To determine the prevalence of gastrointestinal parasites in sheep from the Saquisili sheepfarm in the province of Cotopaxi, 100 samples of feces were taken directly from the rumen taking into account the sex of each animal, which were analyzed by flotation techniques in the laboratory of the Faculty of Agricultural Sciences and Natural Resources of the Technical University of Cotopaxi; in addition, the relationship between the prevalence and the factors of origin and sex was evaluated. The study population consisted of 56% males while 44% were females and the results showed that there is a prevalence of gastrointestinal parasites in the Saquisili animal pen, taking into account the sex variable, it was found that of the 44 female animals, 44 were infected, that is, 100% of this sex, while of 56 male animals, 48 of them were infected, that is, 85.72% of these animals. Therefore, the females had a higher risk of infection. On the other hand, when the infections were analyzed by the variable of origin of the infected animals, it was observed that the greatest number of animals studied came from the city of Saquisili with 50 animals, while the animals coming from the city of Latacunga were 10 and from the town of Tanicuchi came 15 animals and finally, from the town of Tacazo 25 animals were studied.